Exploring Data Traceability Methods in Information Management Within Universities: An Action Research and Case Study Approach - Huang Chen; Zhenying Hu (IEEE Access)
As university information management grows increasingly complex, the demand for seamless data sharing and interaction across various departments and faculties has surged. However, many universities lack a unified platform for data traceability and sensitive information protection, heightening security risks during frequent data exchanges. Furthermore, the uneven allocation of network resources and the absence of effective traffic analysis tools hinder universities from efficiently managing these resources, exacerbating the challenges of network management. Tight budgets further complicate cybersecurity infrastructure development, particularly as universities expand and diversify their disciplines, leading to even more imbalanced funding and constrained investment in network security.To address these challenges, this paper presents a data traceability system integrating Deep Packet Inspection (DPI) and Deep Flow Inspection (DFI) technologies. While DPI and DFI have been extensively studied in the literature, the innovation of this system lies in its hybrid approach, which combines the strengths of both technologies to form a complementary mechanism. This approach is particularly suited to the financial and technical limitations faced by universities. The system is designed for ease of implementation, management, and use, and has been optimized for the unique operational needs of higher education institutions.This research adopts a combination of action research and case study methodologies, starting with small-scale trials to assess system performance before expanding the scope to gather data from broader applications. In addition, this paper introduces the concept of tiered data management for the education sector, offering valuable insights into data classification and traceability within university information systems. The proposed system not only enhances the efficiency of data security management but also provides a practical solution for building future cybersecurity frameworks in higher education.